Aryne cycloaddition: highly efficient chemical modification of graphene - Zhong, Xing; Jin, Jun; Li, Shuwen; Niu, Zhiyong; Hu, Wuquan; Li, Rong; Ma, Jiantai (Chemical communications (Cambridge, England), 2010)
We have developed a simple and efficient approach for the synthesis of chemically converted graphene sheets via aryne cycloaddition under mild reaction conditions. The resulting highly functionalized and thermally stable aryne-modified graphene sheets can be well dispersed in various solvents.